LIVER RESECTION VERSUS RADIOFREQUENCY ABLATION FOR EARLY-STAGE HEPATOCELLULAR CARCINOMA: AN EVIDENCE-BASED NARRATIVE REVIEW OF ONCOLOGICAL OUTCOMES AND TREATMENT SELECTION - Gabriela Kryger; Paweł Jan Babiński; Magdalena Wiśniewska; Zuzanna Karolina Jędrzejczak; Andrzej Józef Horabik; Małgorzata Dmochowska; Julia Hertmanowska; Marta Piotrowska; Krzysztof Chmura; Adrianna Alicja Piekarska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Surgical resection (LR) and radiofrequency ablation (RFA) are established curative options for early-stage hepatocellular carcinoma (HCC), yet their relative benefits remain debated, particularly regarding long-term survival, recurrence control, and patient selection. Objectives: To synthesize contemporary evidence comparing liver resection and radiofrequency ablation for early-stage HCC, with a focus on oncological outcomes, recurrence patterns, perioperative safety, and clinically relevant subgroups. Methods: An evidence-based narrative review was conducted using structured searches of PubMed/MEDLINE and the Cochrane Library. Systematic reviews, meta-analyses, randomized controlled trials, and high-quality observational studies comparing LR and RFA in early-stage HCC were included. Outcomes of interest comprised overall survival (OS), recurrence-free or disease-free survival (RFS/DFS), tumor recurrence, perioperative morbidity, and cost-effectiveness. Findings were synthesized qualitatively. Results: Randomized controlled trials consistently demonstrated no statistically significant difference in overall survival between LR and RFA. In contrast, meta-analyses and propensity-adjusted observational studies suggested improved long-term survival following resection in selected patients with preserved liver function. Across comparative studies, recurrence-free survival and local tumor control consistently favored resection. Subgroup analyses indicated comparable survival outcomes between modalities in patients with very small tumors, impaired hepatic reserve (Child–Pugh class B), and elderly populations, while tumor size and anatomical location emerged as key modifiers of treatment efficacy. Conclusions: Liver resection provides superior local tumor control, whereas overall survival remains largely comparable between modalities in carefully selected patients. Treatment selection should be individualized, integrating tumor characteristics, liver function, patient comorbidities, and procedural risk within a multidisciplinary framework.